Expanding a Lattice-based HVE Scheme - Mochetti, Karina; Dahab, Ricardo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2014: Anais do XIV Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2014.20125, 2014)
Functional encryption systems provide finer access to encrypted data by allowing users to learn functions of encrypted data. A Hidden-Vector Encryption Scheme (HVE) is a functional encryption primitive in which the ciphertext is associated with a binary vector w and the secret key is associated with a special binary vector v that allows "don't care" entries. The decryption is only possible if the vectors v and w are the same for all elements, except the "don't care" entries in v. HVE schemes are used to construct more sophisticated schemes that support conjunctive and range searches. In this work we show how to expand the basic fuzzy IBE scheme of Agrawal et al. (PKC 2012) to a hierarchical HVE scheme. We also show how the version using ideal lattices affects the security proof.